3x + 3(x + 1) + 3(x + 2) = 999
solve in details
Answers
Answer:110
Step-by-step explanation:
Let's solve your equation step-by-step.
3
x
+
3
(
x
+
1
)
+
3
(
x
+
2
)
=
999
Step 1: Simplify both sides of the equation.
3
x
+
3
(
x
+
1
)
+
3
(
x
+
2
)
=
999
3
x
+
(
3
)
(
x
)
+
(
3
)
(
1
)
+
(
3
)
(
x
)
+
(
3
)
(
2
)
=
999
(Distribute)
3
x
+
3
x
+
3
+
3
x
+
6
=
999
(
3
x
+
3
x
+
3
x
)
+
(
3
+
6
)
=
999
(Combine Like Terms)
9
x
+
9
=
999
9
x
+
9
=
999
Step 2: Subtract 9 from both sides.
9
x
+
9
−
9
=
999
−
9
9
x
=
990
Step 3: Divide both sides by 9.
9
x
9
=
990
9
x
=
110
Let's solve your equation step-by-step.
3
x
+
3
(
x
+
1
)
+
3
(
x
+
2
)
=
999
Step 1: Simplify both sides of the equation.
3
x
+
3
(
x
+
1
)
+
3
(
x
+
2
)
=
999
3
x
+
(
3
)
(
x
)
+
(
3
)
(
1
)
+
(
3
)
(
x
)
+
(
3
)
(
2
)
=
999
(Distribute)
3
x
+
3
x
+
3
+
3
x
+
6
=
999
(
3
x
+
3
x
+
3
x
)
+
(
3
+
6
)
=
999
(Combine Like Terms)
9
x
+
9
=
999
9
x
+
9
=
999
Step 2: Subtract 9 from both sides.
9
x
+
9
−
9
=
999
−
9
9
x
=
990
Step 3: Divide both sides by 9.
9
x
9
=
990
9
x
=
110
Let's solve your equation step-by-step.
3
x
+
3
(
x
+
1
)
+
3
(
x
+
2
)
=
999
Step 1: Simplify both sides of the equation.
3
x
+
3
(
x
+
1
)
+
3
(
x
+
2
)
=
999
3
x
+
(
3
)
(
x
)
+
(
3
)
(
1
)
+
(
3
)
(
x
)
+
(
3
)
(
2
)
=
999
(Distribute)
3
x
+
3
x
+
3
+
3
x
+
6
=
999
(
3
x
+
3
x
+
3
x
)
+
(
3
+
6
)
=
999
(Combine Like Terms)
9
x
+
9
=
999
9
x
+
9
=
999
Step 2: Subtract 9 from both sides.
9
x
+
9
−
9
=
999
−
9
9
x
=
990
Step 3: Divide both sides by 9.
9
x
9
=
990
9
x
=
110
Answer:
3x+3(x+1)+3(x+2)=999
3x+3x+1+3x+6=999
3x+3x+3x+1+6=999
9x+7=999
9x=999-7
9x=992
x=992÷9
x=110.22